PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. RADJAWALI - Andri Susilo; Hendriyatna Hendriyatna (Universitas La Tansa Mashiro, 2019)
Employee performance is a matter that must be considered by every company. Because the survival of the company depends on the performance of employees that occur in the company. This study aims to determine (1) the effect of compensation on employee performance (2) the influence of the work environment on employee performance (3) the effect of compensation and work environment simultaneously on employee performance. The method used is a quantitative method with a survey. Samples were taken using total sampling techniques, namely 41 employees of CV Radjawali Pandeglang. Data collection tool uses a Likert scale questionnaire. Data analysis techniques using classical assumptions, correlation coefficients, deteremination and multiple linear regression and hypothesis testing using the t test (partial) and F test (simultaneous). Testing statistics using the SPSS V.20 application program. T test results show that compensation has a significant effect on employee performance and the work environment has a significant effect on employee performance. While the F test results show that compensation and work environment simultaneously have a significant effect on employee performance. Based on the results of the study it can be concluded that (1) partially compensation and work environment significantly influence the performance of employees of CV Radjawali Pandeglang (2) compensation and work environment simultaneously significantly influence the performance of employees of CV Radjawali Pandeglang.